A study of human mobility behavior dynamics: A perspective of a single vehicle with taxi. (May 2016) - Yao, Can-Zhong; Lin, Ji-Nan
Highlights: Distance distribution of human mobility with single vehicle may follow power-law. Fare and mobility distance follows piecewise function is influential. Waiting time is important in the piecewise function to cause the distribution. Decision way of power law performs better than exponential way to explain the phenomenon. Abstract: In this paper, we first research on the distance distribution of human mobility with single vehicle based on the driving data from a taxi company in South China. Different from conventional exponential distribution, we discover the mobility distance with taxi follows power-law distribution. Further, we proposed a model which may explain the mechanism for the power-law distribution: mobility distance is constrained by time and fare. Specifically, the relationship between fare and mobility distance follows piecewise function, and responds to individual sensitivity; the relationship between time and mobility distance follows significant logarithmic relationship. These two factors, especially the logarithmic relationship between time and mobility distance, may contribute to a power-law distribution instead of an exponential one. Finally, with a simulation model, we verify the significant power-law distribution of human mobility behavioral distance with a single vehicle, by supplementing factors of waiting time and fare.